Intimate partner violence against women during pregnancy in Tripura: a hospital based study - Bhattacharjya, Himadri; Deb, Durba (International Journal of Research in Medical Sciences, 2017)
Background: Intimate partner violence is increasing day by day and has become a matter of public health concern. Methods: To estimate the prevalence of intimate partner violence during pregnancy, to find out the pattern of violence and its determinants, a hospital based cross-sectional study was conducted among 1005 women admitted in the maternity wards of Agartala Government Medical College and Mohanpur Community Health Centre using multistage sampling and structured interview schedule during 20th November 2009 to 19th November 2010. Descriptive statistics, chi-square test and binary logistic regression analysis were used. Results: Mean age of the study women was 23.21 (± 4.229). Prevalence of physical assault during pregnancy was 23.8 %, verbal abuse 40.6 %, forced intercourse 21.2 %. Violence was faced by 43.2 % women before pregnancy, and in 29.5 % cases, it continued during pregnancy also. 37.815 % violence occurred without any reason; 34.873 % due to financial matters, 12.605 % due to family affairs, 6.302 % for not giving birth to son, 8.403 % due to household work and suspicion of infidelity. Violence was more prevalent among Christian, daily labours (n = 31, 75.6%), illiterate and rural women. Women faced more violence from addicted husbands (n = 239, 26.3%) and in families where decision makers were illiterate (n = 201, 47.2%). Conclusions: Improving literacy, eliminating addiction and marriage of women with men of lesser age difference may help in minimizing intimate partner violence in Tripura.